Improving the Mechanical, Water Vapor Permeability, Antimicrobial properties of Corn-Starch/Poly Vinyl Alcoholfilm (PVA): Effect of Rice husk fiber (RH) & Alovera gel(AV). Issue 1 (March 2020) - Mallick, Nirlipta; Soni, A.B; Pal, Dharm
Abstract: Essentially because of ecological points, petroleum-based plastics are being supplanted by natural polymers. In the most recent decades, the starch idea is outstanding as a green material. Because of the developing interest for Starch biodegradable materials and the film-forming capacity it has been significantly utilized in the food packaging area.Polyvinyl alcohol (PVA) is one of the synthetic biodegradablematerials that has the upsides of good film formation and high thermal stability. It has been utilized as coatings, packaging material, and in drug delivery applications. Aloe vera(AV) gel, an individual is a promising material in food preservation and has great antimicrobial and anti-inflammatory properties. Because of its filmforming capacity, it has been utilized in the edible film and coatings. Naturalfibers from agricultural waste are finding their significance in the food packaging sector because of the numerous favourable circumstances, for example, their lightness, minimal effort and being earth amicable. The rice husk (RH) is acquired from agro-industrial waste, can be utilized as filler in different bio compositesmaterials. Themain purpose of this examination was to investigate the impact of Rice husk fiber and Alovera gel on the Mechanical, Water Vapor Permeability, Antimicrobial properties of Corn-Starch based film.